Kids’ behaviour at birth in local goats of Rohilkhand - Dhiman, Chitra; Chabra, A K (The Indian Journal of Animal Sciences, 2005)
The present study was conducted during December 2002 to April 2003, at sheep and goat production farm, IVRI Izatnagar, on 15 pregnant local goats of Rohilkhand region. The does were divided into 3 treatment group(1 ,2 and 3) and were fed different levels of concentrate mixture, viz. 350 g/d (control), 420g/d, 28Og/d, respectively, alongwith ad lib.green oat (in weighed quantity) from 4 weeks prior to kidding up to the date of kidding. The kids born from these 15 goats were utilized for studying the various behavioral developments from birth up to 6 hr and for survival rate till 8 weeks of their age. The present study revealed the birth of 19 kids; out ofwhich only 15 survived (78.95%). The sex: ratio between male and female was 9:10. the sex of the kids significantly affected the development of various behaviour among kids within 6 hr after birth and male kids took more time to learn various behavioural activities after birth than female kids. The number of attempts for teat-seeking significantly higher in kids belonging to treatment group 1 or treatment group 2 than those belonging to treatment group 3. Higher pre-kidding body-weight of does led to lesser number of attempts to first stand, earlier standing and earlier urination by their kids. The number of attempts to first stand made by kids with higher birth-weight, were signilicantly lower than the kids with lower birth-weight.